Knowledge, attitude and dispensing practice of the pharmacists related to complementary alternative medicines in the Riyadh region of Saudi Arabia: a cross-sectional descriptive study - Hanan M. Al-Yousef; Ahmad H. Alghadir; Amir Iqbal (BMC, 2022)
Abstract Background The use of complementary alternative medicines (CAMs) has risen globally in recent times. Such medications are exclusively and readily available in the Riyadh region of Saudi Arabia through community pharmacies and other retail outlets, exposing the consumers to various risks like harmful drug interactions. These situations take pharmacists to a responsible position where they should provide evidence-based information to help consumers make safe consumption. The consumption of CAMs can be ensured safe if pharmacists have appropriate knowledge and training about their use, dosing, side effects, etc. This study aimed to investigate and evaluate the pharmacist's factual knowledge, perception and dispensing practice related to various aspects of CAMs based on gender and experience. Methods The study followed a structured self-administered questionnaire-based cross-sectional survey design. Out of 200, with a response rate of 89.5%, 179 pharmacists (115 males; 64 females) from the Riyadh region of Saudi Arabia participated in this study. The knowledge scores of male and female pharmacists were compared using an unpaired t-test. The correlation between pharmacists' knowledge and their work experience was determined using Pearson's correlation coefficient test, keeping the significance value at p < 0.05. Results Almost all the respondents (99%) reported that they had never attended any lecture or course related to CAMs. Results show low knowledge scores, indicating poor respondents' knowledge concerning the use of CAMs. No significant difference was observed in knowledge scores based on gender, and no significant correlation between pharmacists' knowledge scores and their work experiences. Conclusion Therefore, the study concluded that both male and female pharmacists possess equal knowledge concerning the use of CAMs, and their work experience doesn't differentiate in their knowledge. Various factors like lack of time, etc., prevented respondents from interacting with patients. Regular organization of mandatory continuing education programs about the safe use of CAMs that can improve their knowledge is recommended. In addition, establishing a pharmacy connection network system can enhance patient monitoring and CAMs vigilance. This study lays a foundation for further work to assess pharmacists' knowledge and practice patterns in Saudi Arabia. Trial registration Not applicable.